Charles Rosen, Music and Sentiment (2010) - Tinney, Hugh (Journal of the Society for Musicology in Ireland, 2012)
A review of Charles Rosen, Music and Sentiment (New Haven & London: Yale University Press, 2010), ISBN 978-0-300-12640-2.